Performing head-to-toe assessment - Denman, Susan; Woodruff, Kathleen M.; Springhouse Corporation (Springhouse, PA : Springhouse Co., 2000)
Gives sight-and-sound approach to mastering head-to-toe assessment skills. Includes detailed instructions on how to skillfully and systematically assess the head, neck, thorax, breasts, abdomen, arms, legs, genitalia, and rectum ; step-by-step demonstrations of proper inspection, palpation, percussion, and ausculation techniques ; clear explanations of the how's and why's of head-to-toe assessment ; tips on how to interpret and document assessment findings
Keywords: Physical Examination -- methods -- Nurses' Instruction; Medical History Taking -- methods -- Nurses' Instruction